Patient satisfaction in the management of mild-to-moderate ulcerative colitis: Results of a Delphi study among patients and physicians. Issue 10 (October 2016) - Casellas, Francesc; Ginard, Daniel; Riestra, Sabino
Abstract: Goals: To determine factors contributing to satisfaction with treatment in mild-to-moderate ulcerative colitis (UC) from both the patients and the physicians perspectives. Background: Despite the impact of UC on different aspects of daily life, patient's and physician's satisfaction with clinical management has been poorly evaluated. Study: A Delphi study involving 22 patients and 20 clinicians was conducted. The patient's questionnaire included 285 items regarding diagnosis, treatment, and follow-up, whereas the physician's questionnaire added 32 specific items for clinicians. Relevance of items was scored from 1 (not at all important) to 9 (very important). Recommendations were based on very highly rated items. Results: Most items were rated consistently by patients and physicians with some exceptions. Patients emphasized the choice of moderate flare-ups to be followed at the hospital setting rather than in primary care as well as to be informed on aspects, such as diet and impact of UC on their health and lifestyle. Treatment-related efficacy, safety, and improved quality of life were relevant for both patients and physicians. Physicians believed that to reduce pill burden was a crucial aspect to improve patient's satisfaction. Patients preferred oral administration treatment over rectal treatment. Conclusions: The study identified specific aspects related to the management of mild-to-moderate UC that both patients and physicians considered to be highly relevant for patient satisfaction. Recommendation based on these factors would be important at the time of designing and implementing strategies targeting satisfaction in UC patients.